The Importance of Choosing the Right Majors in The University and The Respective Career Prospects - Ponziani, Regi Muzio; Yuwono, Arleen Herawaty; Gulo, Yupiter; Jonathan, Aries; Syahrian, Syahrian; Gunawan, Hery; Wardy, Andes (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
High school and vocational school students will continue their education to the university level. At the university level, there are various majors available. The chosen major will most likely determine the career prospects that these students will pursue. Recognizing the importance of this, SMA Muhammadiyah 25 Pamulang and Trisakti School of Management held a seminar on the importance of choosing a major for students in the social humanities track. Two majors were introduced, namely Accounting and Management. The community service activity began with an introduction to the majors and career prospects in Accounting and Management, and ended with a Q&A session. The speakers also asked several questions and made observations to test the students’ understanding of the material presented. In general, the community service activity ran very well.